Professional elementary teachers in the digital era: A systematic literature review - Hamidulloh Ibda; Ibnu Syamsi; Rukiyati Rukiyati (Institute of Advanced Engineering and Science, 2023)
Teachers of elementary school must be professional and have digital skills in Revolution 4.0, and Society 5.0 age progresses. This article includes a thorough assessment of the research on elementary school teachers’ professional competence, professional development, and digital competence. This research is needed to determine what professional elementary school teachers did and why they should be professionals in the digital age. The writing of this systematic review of literature articles was assisted by the Publish or Perish 7, Mendeley, VOSviewer, and Nvivo 12 Plus application. The search for articles in Scopus indexed journals is limited to the last 11 years (2010-2021). From the search results, there were 100 Scopus indexed articles, then articles were selected according to compatible themes into 31 selected articles. Professionals’ teacher, professional development, pedagogical content knowledge, teacher professional development, professional development program, and professional competence are among the findings of the theme/topic. The articles were analyzed according to the topics determined through the NVIVO 12 Plus. This article contributes to subsequent research and becomes a study for the theme of professional elementary school teachers and teacher competence in the digital era.